Advancements in Clinical Practice: A Comprehensive Review of Emerging Trends in Medical Development - Alajmi , Abduruhman Fahad G; Otaibi, Saud Bin Eid Al; Al Zahir, Zahra Jaffer; Almohaishi, Safa Ali Mohammed; Aleinzii, Khalid Faris Salem; Almutawa, Abdulaziz Khalifa Ali; Alawadh, Ekram Essa Ayesh; AlHubail , Aqeelah Abdullah; Alakloby, Rajawy Mohad Sultan; Alsadan , Mashel Abdullah (Journal of Ecohumanism, 2024)
This review article explores the latest advancements in clinical practice, focusing on emerging trends that are transforming healthcare delivery and patient outcomes. Key developments discussed include telemedicine and remote patient monitoring, personalized and precision medicine, artificial intelligence (AI) and machine learning (ML) in diagnostics, robotics and automation in surgery, as well as mobile health applications and wearable devices. Each of these advancements has the potential to enhance the accessibility, accuracy, and efficiency of clinical care. However, these innovations also introduce challenges, such as concerns about data privacy, ethical considerations surrounding AI, and the need for updated regulatory frameworks. The review highlights how these trends contribute to improved patient engagement, cost efficiency, and overall healthcare quality. By examining both the benefits and challenges associated with these developments, this article underscores the importance of innovation in driving the future of clinical practice. Recommendations for future research and policy are also provided to support the continued evolution of healthcare practices.